2015
DOI: 10.1186/s12917-015-0382-0
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of a unique SYBR Green real-time RT-PCR assay for quantification of five major cytokines in cattle, sheep and goats

Abstract: BackgroundToday, when more than 60% of animal diseases are zoonotic, understanding their origin and development and identifying protective immune responses in ruminants are major challenges. Robust, efficient and cost-effective tools are preconditions to solve these challenges. Cytokines play a key role in the main mechanisms by which the immune system is balanced in response to infectious pathogens. The cytokine balance has thus become the focus of research to characterize immune response in ruminants. Curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 37 publications
(52 reference statements)
2
31
0
Order By: Relevance
“…The expression of ISG15 and Mx2 genes was examined using quantitative RT-PCR (LightCycler® FastStart DNA Master SYBR Green I, Roche); the gene expression was normalized to GAPDH [19]. The primer pairs for the detection of the genes are as follows—ISG15 (NM_174366) forward: GGTATCCGAGCTGAAGCAGTT, reverse: ACCTCCCTGCTGTCAAGGT (131–217, 86 bp); Mx2 (NM_173941) forward: CTTCAGAGACGCCTCAGTCG, reverse: TGAAGCAGCCAGCAATAGTG (2071–2302, 231 bp); and GAPDH (XR_082746) forward: GATTGTCAGCAATGCCTCCT, reverse: GGTCATAAGTCCCTCCACGA (546–638, 92 bp).…”
Section: Methodsmentioning
confidence: 99%
“…The expression of ISG15 and Mx2 genes was examined using quantitative RT-PCR (LightCycler® FastStart DNA Master SYBR Green I, Roche); the gene expression was normalized to GAPDH [19]. The primer pairs for the detection of the genes are as follows—ISG15 (NM_174366) forward: GGTATCCGAGCTGAAGCAGTT, reverse: ACCTCCCTGCTGTCAAGGT (131–217, 86 bp); Mx2 (NM_173941) forward: CTTCAGAGACGCCTCAGTCG, reverse: TGAAGCAGCCAGCAATAGTG (2071–2302, 231 bp); and GAPDH (XR_082746) forward: GATTGTCAGCAATGCCTCCT, reverse: GGTCATAAGTCCCTCCACGA (546–638, 92 bp).…”
Section: Methodsmentioning
confidence: 99%
“…The amount and duration of these herbs were tested in this study by using a different amount of CEVASTIM in different durations. The method, real-time RT-PCR to estimate cytokine expression levels used in this study was also used by many investigators (Dapas et al, 2014;Konnai et al, 2003;Puech, Dedieu, Chantal, & Rodrigues, 2015). Results of previous studies have indicated that cytokine gene expression usually increases after 72-96 hours of immunization (Dar, Hajam, Suryanarayana, Kishore, & Kondabattula, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…YWHAZ codes for Tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein, zeta polypeptide and was earlier reported to be a suitable reference gene for bovine samples (Spalenza et al, 2011). Previously reported primers which bind at the exon-exon junctions were used in this study (Yamada et al, 2009;Puech et al, 2015). Group I represents bovine PBMC treated with live M. bovis at MOI of 100:1 and group II represents untreated control.…”
Section: Resultsmentioning
confidence: 99%